Killer woman blues why Americans can't think straight about gender and power - DeMott, Benjamin 1924-2005 (Boston Houghton Mifflin, 2000)
The author examines the view that women feel they must act like men to succeed and how this behavior is reshaping American society.
1. "For This We Chained Ourselves to Fences?" 1. Women-Becoming-Men: Voices of Kickbutt Culture. 2. Anatomy of Gender Shift (1): Politics and Personae. 3. Anatomy of Gender Shift (2): Hardening Processes. 4. The Media's Love-Hate Relationship with Women-Becoming-Men. 5. Killer Women and Corporate Kindness -- 2. A Vision of Variousness. 6. Gender Flexibility: The Front Line. 7. The Pursuit of Compositives. 8. Spies in the House of Love. 9. A Community of Beings in a Single Self -- 3. Whiplash Injuries. 10. Positivity Lost. 11. The Detachment Trap. 12. Self-Censorship and Double Binds. 13. Shades of Darkness -- 4. Traducing History vs. Growing Capital. 14. Three Styles of Nostalgia. 15. Achievements in Variousness: A Conclusion.
Includes bibliographical references.
Keywords: Sex role -- United States; Power (Social sciences) -- United States